2015
DOI: 10.1155/2015/652017
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 185delAG Mutation Enhances Interleukin-1βExpression in Ovarian Surface Epithelial Cells

Abstract: Familial history remains the strongest risk factor for developing ovarian cancer (OC) and is associated with germline BRCA1 mutations, such as the 185delAG founder mutation. We sought to determine whether normal human ovarian surface epithelial (OSE) cells expressing the BRCA1 185delAG mutant, BRAT, could promote an inflammatory phenotype by investigating its impact on expression of the proinflammatory cytokine, Interleukin-1β (IL-1β). Cultured OSE cells with and without BRAT were analyzed for differential tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Experiments with short term cultures of primary fimbrial fallopian tube cells ( Supplementary Fig. 4 ) and with the SKOV3 ovarian cancer cell line demonstrated that NF-κB -activating inflammatory signals (that is, TNF-α and IL1-β), which are known to (i) be released in the pelvis under conditions known as risk factors for HGSEMCs (that is, pelvic inflammatory disease or frequent ovulation associated with the need for repeated repair of ovulatory defects in close proximity to the fimbrial tube) and (ii) be more abundant in women with a family history due to a BRCA1 mutation 27 28 29 , lead to increased expression of AID ( Fig. 4b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments with short term cultures of primary fimbrial fallopian tube cells ( Supplementary Fig. 4 ) and with the SKOV3 ovarian cancer cell line demonstrated that NF-κB -activating inflammatory signals (that is, TNF-α and IL1-β), which are known to (i) be released in the pelvis under conditions known as risk factors for HGSEMCs (that is, pelvic inflammatory disease or frequent ovulation associated with the need for repeated repair of ovulatory defects in close proximity to the fimbrial tube) and (ii) be more abundant in women with a family history due to a BRCA1 mutation 27 28 29 , lead to increased expression of AID ( Fig. 4b ).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, cell ‘non-autonomous' factors known to be strongly associated with HGSEMC risk (that is, high number of ovulations and pelvic inflammatory disease 34 ) could lead to aberrantly high AID. Some, although rather preliminary, support for a cell ‘non-autonomous' mechanism comes from the observation that a BRCA1 mutation enhances Interleukin-1β expression in ovarian surface epithelial cells 29 , and that BRCA mutation carriers' associated epigenetic mis-programming of immune cells 18 may lead to subtle immune defects which in turn facilitate microbial ascension from the vagina to the fallopian tube. Additional evidence for a cell ‘non-autonomous' factor comes from our previous observation that BRCA mutation carriers demonstrate higher oestrogen levels in the luteal phase 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The BRCA1 185delAG mRNA is predicted to produce a short, approximately 5-kDa peptide (E23fsX17). Although this peptide has not been detected endogenously, exogenous overexpression of a BRCA1 peptide consisting of aa 1-23fsX17 was reported to induce phenotypes not associated with full-length BRCA1, including enhanced IL-1β expression, and to promote apoptosis (45,46). However, endogenously generated small peptide products normally located in the structured RING region of the protein may not be folded and are likely to be degraded.…”
Section: Methodsmentioning
confidence: 99%
“…BRCA1 (breast cancer 1) 185delAG mutation in ovarian epithelial cells allows IL-1β expression [ 124 ]. BRCA1 helps the sensing of herpes virus DNA and the activation of caspase-1 and IL-1β production [ 125 ].…”
Section: Pro-and Anti-tumor Effects Of Il-1βmentioning
confidence: 99%